2016
DOI: 10.1242/jcs.186338
|View full text |Cite
|
Sign up to set email alerts
|

CEP295 interacts with microtubules and is required for centriole elongation

Abstract: Centriole duplication is a tightly ordered process during which procentrioles are assembled in G1-S and elongate during S and G2. Here, we show that human CEP295 (Drosophila Ana1) is not essential for initial cartwheel assembly, but is required to build distal half centrioles during S and G2. Using super-resolution and immunogold electron microscopy, we demonstrate that CEP295 is recruited to the proximal end of procentrioles in early S phase, when it is also localized at the centriolar microtubule wall that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 39 publications
(98 reference statements)
0
90
0
Order By: Relevance
“…Similarly, Manandhar et al 5 found using immunogold labeling that CETN1/2 associates with microtubules at the point where the microtubules begin to splay in the DC, the same site where we observed the DC rods. This rod organization has never been described for any centriolar protein; most centriolar proteins and the structures within the distal lumen of a centriole exhibit radial symmetry in the form of disk and column structures 3033 . Together, these findings demonstrate that several centrosomal proteins have an atypical distribution in the DC (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Similarly, Manandhar et al 5 found using immunogold labeling that CETN1/2 associates with microtubules at the point where the microtubules begin to splay in the DC, the same site where we observed the DC rods. This rod organization has never been described for any centriolar protein; most centriolar proteins and the structures within the distal lumen of a centriole exhibit radial symmetry in the form of disk and column structures 3033 . Together, these findings demonstrate that several centrosomal proteins have an atypical distribution in the DC (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…It will be interesting to investigate whether Cep295 molecules on the mother centriole are rearranged and moved to the assembly site of a procentriole to trigger centriole formation. It should also be noted that while this study was under review, another studies reported that Cep295 and Ana1 regulate centriole elongation in human42 and Drosophila cells43, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Centriole length can also be modulated by deregulation of proteins implicated in building the distal halves of centrioles, including the WD40 protein POC1 ( P roteome O f C entriole protein 1) 55 , the centrin-binding protein hPOC5 56 , or the microtubule binding protein CEP295 (Ana1 in Drosophila ) 57,58 . Interestingly, depletion of CEP295 not only impairs the recruitment of hPOC5 and POC1, but also blocks the acetylation and glutamylation of centriolar microtubules 57 . In vertebrates, these tubulin modifications accumulate on centrioles as well as cilia, and polyglutamylation is required for long-term stability of centriolar microtubules 59 .…”
Section: Centrosome Structure and Assemblymentioning
confidence: 99%